1998
DOI: 10.1289/ehp.98106s1349
|View full text |Cite
|
Sign up to set email alerts
|

The use of biochemical and molecular parameters to estimate dose-response relationships at low levels of exposure.

Abstract: Biomarkers based on alterations in molecular and biochemical parameters may be useful in chemical risk assessment for establishing the presence of an exposure, ranking relative risks among exposed individuals, and estimating risks at low levels of exposure. Because it is unlikely that the relation between toxic responses and the degree of alteration in the biomarker is equivalent at all doses, quantification of risks at low levels is not necessarily more accurate using these biomarkers for extrapolation. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Many underlying mechanisms may be responsible for hormesis, such as an overcompensation to maintain homeostasis at low doses of a toxicant (Calabrese and Baldwin 2001). For example, exposure to dioxin-like compounds can create a U-shape response at low doses, which coincides with the multiple different effects of dioxins, such as cell proliferation, toxicity, and mitosuppression for tumour induction (Andersen and Barton 1998). Further investigation would be needed to validate and explain the inverted U-shaped response measured for cyp2b5 in C. serpentina livers.…”
Section: Resultsmentioning
confidence: 97%
“…Many underlying mechanisms may be responsible for hormesis, such as an overcompensation to maintain homeostasis at low doses of a toxicant (Calabrese and Baldwin 2001). For example, exposure to dioxin-like compounds can create a U-shape response at low doses, which coincides with the multiple different effects of dioxins, such as cell proliferation, toxicity, and mitosuppression for tumour induction (Andersen and Barton 1998). Further investigation would be needed to validate and explain the inverted U-shaped response measured for cyp2b5 in C. serpentina livers.…”
Section: Resultsmentioning
confidence: 97%
“…При анализе причин, определивших отсутствие различий в уровнях экспрессии cyp1a2 между этими выборками, мы обратили внимание на чрезвычайную вариабельность зарегистрированных по-Таким образом, использованные в работе показатели экспрессии генов и активности ретротраспозонов отражают эффекты начальных ответных реакций организма на действие факторов среды обитания в условиях длительного хронического воздействия диоксинов, загрязняющих среду в малых концентрациях. В этой связи отметим, что при изучении проявлений этих эффектов во взаимосвязи с мерами токсической нагрузки диоксинов на организм важно учитывать вероятность нелинейного характера таких взаимосвязей, когда низкие их дозы могут быть более активны в отношении вызываемых эффектов (парадоксальное действие диоксинов с нелинейными (U-образными) кривыми зависимости «доза -эффект») [3,[28][29][30]. Более того, следует учитывать множественные сигнальные пути и механизмы с участием AhR, вовлекаемые в ответные реакции на низкие дозы с самых ранних этапов онтогенеза и способные изменять функциональную активность иммунной, нервной, репродуктивной и других систем организма.…”
Section: результаты и обсуждениеunclassified
“…Lutz et al (2005) provide examples showing that the apparent threshold often observed in bioassay data may be spurious and misleading for low-dose extrapolation and human cancer risk assessment. Using TCDD as an example, Andersen and Barton (1998) have also provided an explanation of how a U-shaped dose-response can occur as a result of a combination of various toxicological responses each of which has a different dose-response. For instance, a U-shaped dose-response can result if the compound at issue has a mitosuppressive effect on a subset of initiated cells with some specific mutations; in this case, response at low doses would decrease to be lower than the control group but would increase with increasing dose.…”
Section: Introductionmentioning
confidence: 99%